STYLISTIC-NARATOLOGY VERSES OF SULAIMAN'S STORY INHERITING THE KINGDOM OF DAUD - Amrulloh, Muhammad Afif; Latif, Abdul; Kamal, Helmi; Mahliatussikah, Hanik; Fauziah, Asti (Arabi : Journal of Arabic Studies, 2022)
The story of Sulaiman inheriting the kingdom of Daud was presented in a distinctive language style. In addition to having unique preferences and deviations in pronunciation, it also contained the relevance of the story to the monotheistic da'wah of Muhammad. This study intended to analyze the secrets of the existing figurative language as well as the semiotic meaning of the story and its relevance to the prophet's monotheism mission. This research used qualitative research and descriptive research methods. The research data comes from the qaşaş verse which is the source of the material for this research. Data was collected by using the note-taking technique. The translational equivalent technique carried out the data analysis technique. The results of this study from the stylistic aspect found that the selection of letters, the selection of pronunciation, the selection of sentences, accentuation of the dialogue in the story verse. This research contributed to the development of literary studies that combine stylistic analysis and narratology in one study of the story of Al-Qur'an.